Model Optimalisasi Manajemen Strategik Berbasis Balanced Scorecard untuk Membangun Keunggulan Kompetitif di Universitas Islam Kuantan Singingi - Ikrima Mailani; Zulhaini; Fitra Wahyuni (Yayasan Madinah Al-Aziziyah, 2026)
Islamic higher education institutions in Indonesia face persistent challenges in building integrated, measurable strategic management systems that are oriented toward competitive advantage. Many institutions experience a strategy gap between institutional-level planning and unit-level implementation, with performance indicators that remain fragmented, human resource development that is reactive rather than planned, and budget allocations that are disconnected from strategic priorities. This study aims to formulate a strategic management optimization model using the Balanced Scorecard approach to build the sustainable competitive advantage of Universitas Islam Kuantan Singingi. The study employed a qualitative approach with a case study design conducted in 2025. Data were collected through in-depth semi-structured interviews with 12 informants comprising university leadership, lecturers, and administrative staff, structured observation, and document review, then analyzed using the Miles, Huberman, and Saldaña model through data reduction, data display, and conclusion drawing. Data validity was ensured through four criteria based on Lincoln and Guba standards: credibility, transferability, dependability, and confirmability. The findings reveal three key empirical gaps in the university’s strategic management: the strategic plan has not been fully internalized across faculties and work units; the performance measurement system remains partial and lacks cause-and-effect integration across perspectives; and human resource development is reactive rather than systematically anchored to institutional strategic direction. Based on these empirical findings, an optimization model comprising six interrelated stages was developed: strategic environment analysis, strategic direction formulation, Balanced Scorecard-based strategy map development, key performance indicator formulation, strategic program implementation, and continuous monitoring and evaluation. The four Balanced Scorecard perspectives; learning and growth, internal business processes, stakeholders, and financial form a value chain in which each perspective strengthens the next, collectively building institutional competitive advantage. Islamic values, including amanah, honesty, quality, and sustainability, function as an authentic layer of differentiation embedded throughout the entire model, creating institutional character that cannot be replicated through financial investment alone. This study contributes a contextual Balanced Scorecard framework that specifically integrates Islamic institutional character, governance quality, and competitive advantage-building within a single operational model addressing a gap in the existing literature on strategic management in Indonesian Islamic higher education.